Peningkatan Teknik Dasar Renang Gaya Punggung Dan Keselamatan Berenang Bagi Mahasiswa Baru Penjaskesrek - Ahmad Adil; Sahabuddin; Muhammad Ishak; Awaluddin Awaluddin; Ishak Bachtiar (PT. Mediatama Zayna Indonesia, 2026)
Improving basic backstroke swimming techniques and swimming safety aspects is a crucial requirement for new Penjaskesrek students as future educators and sports practitioners. Initial observations indicate that most students still experience difficulties in coordinating basic backstroke techniques and lack understanding of water safety procedures. This condition has the potential to reduce the quality of swimming learning at the college and school levels. Based on these problems, this community service activity aims to improve mastery of basic backstroke swimming techniques and understanding of swimming safety through a structured training approach. The community service activity was carried out at the FIKK UNM Swimming Pool and involved 35 new PJKR students. The methods used included initial observation, providing theoretical material, technique demonstrations, gradual exercises, water safety simulations, and evaluations in the form of pre-tests and post-tests. Raw data were collected to measure aspects of swimming skills before and after training. From 20 structured data samples, the pre-test score obtained an average of 59.55 and a post-test score of 75.65. Data analysis was carried out using a paired sample t-test statistical test via SPSS to determine the significance of skill improvements. The descriptive test results showed an increase in backstroke technique scores from a minimum of 55 to 83 in the post-test. The correlation test produced a relationship value of 0.82, indicating consistent improvement in learning outcomes for each participant. The paired sample t-test results obtained a value of t = -17.35 with a significance of 0.000 (p < 0.05), indicating that the training had a significant effect on improving swimming ability. Overall, the training activities implemented were proven effective in improving basic backstroke technique skills and understanding of swimming safety. It can be concluded that structured training that combines theory, demonstration, direct practice, and evaluation can provide significant improvements in the swimming abilities of new students. This activity is important to continue and develop to become part of a sustainable swimming development program on campus